1979
DOI: 10.1029/jc084ic04p01710
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric arsenic over marine and continental regions

Abstract: Particulate and vapor concentrations of atmospheric as have been measured over various marine and continental areas. Particulate samples were collected on double Whatman 41 filters. Particulate‐vapor samples were collected using an in‐line filter system with a 0.45‐μm pore size Nuclepore filter as a particle prefilter in front of two Whatman 41 filters impregnated with tetrabutylammonium hydroxide and glycerol for vapor As collection. Arsenic determinations were by destructive neutron activation. The data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…For these estimates, arsenic is assumed to be entirely in particulate form and contained totally within the troposphere. Walsh et al [ 1979] have shown that vapor phase As constitutes less than 10% of the As present in near-surface air over marine and continental areas and that the major mass of As in these regions is on relatively small particles (d _< 1 #m). Representative surface concentrations of atmospheric arsenic in marine and continental areas have been estimated from measurements Area, m:…”
Section: The Global Tropospheric Burden Of Particulate Arsenicmentioning
confidence: 99%
See 3 more Smart Citations
“…For these estimates, arsenic is assumed to be entirely in particulate form and contained totally within the troposphere. Walsh et al [ 1979] have shown that vapor phase As constitutes less than 10% of the As present in near-surface air over marine and continental areas and that the major mass of As in these regions is on relatively small particles (d _< 1 #m). Representative surface concentrations of atmospheric arsenic in marine and continental areas have been estimated from measurements Area, m:…”
Section: The Global Tropospheric Burden Of Particulate Arsenicmentioning
confidence: 99%
“…The arsenic emission factor of 5.7 X 10 -8 is the amount of arsenic per gram of sea salt [Pytkowicz and Kester, 1971]. The percent of less than 5-#m diameter particulates for this source is based on a mass rnediam diameter (MMD) of 5-#m for atmospheric sea-salt particles [Duce et at., 1976;Walsh et at., 1979]. The total arsenic production for this size range is calculated to be 0.028 X 10 •' g/yr.…”
Section: Natural Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the air, arsenic Is primarily associated with particles, although II also has been observed at much tower levels In the gas phase (Johnson and Braman 1975;Walsh et al 1977Walsh et al , 1979Appel et al 1984 (Solomon 1984), and the City of Industry, Los Angeles County, CaiHomla (Rabano et al 1989). The City of Industry slle was located wllhln 1 kilometer of a known high temperature IOUfCe of arsenic (a secondary lead smeller (ARB 1t90bJ).…”
Section: Atmospheric Arsenicmentioning
confidence: 99%